Gender stereotypes of saving dental health among students - M. K. Makeeva; T. A. Mityushkina; E. T. Melkova; V. A. Maltseva; A. V. Shegai; M. V. Kostinskaya (Эндодонтия Today)
AIM. To conduct a literature review and establish the relationship between gender stereotypes and dental health saving among students and to conduct our own analysis among higher education institutions such as: RUDN, RNIMU, MIREA.MATERIALS AND METHODS. A systematic literature review in the electronic databases of Google Scholar and Pubmed was conducted. Articles with content based on identifying the role of gender on oral health among 18–25-year-olds were reviewed. Sixty articles were reviewed, of which 10 from Pubmed and 50 from Google Scholar were selected. After selecting articles according to criteria, the total number of studies was 30. In addition, we conducted our own analysis among universities such as: RUDN, MIREA, RNIMU. 66 people (48 girls and 18 men) participated in the survey.RESULTS. We established the relationship between gender stereotypes and saving dental health, but we do not exclude that the level of oral health among students is individual and depends only partly on gender.CONCLUSION. It is possible to note the influence of gender stereotypes regarding saving dental health. Girls are more careful about the state of oral cavity and health in general. This conclusion is based on the increased frequency of visits to the dentist for preventive examinations. The male part of the population, due to lack of knowledge in the field of prevention, improperly care for their oral cavity, this is expressed in the wrong brush, its coarser use and lack of instructions for daily brushing. The attitude of men towards the dentist plays an important role. Due to lack of habit and less awareness of health issues, they are more likely to be exposed to discomfort and stress during the appointment than girls. In conclusion, we would like to say that gender stereotypes have a place, but still the level of dental health among students is individualized and only partly depends on gender.